Level of Community Knowledge in RT.006/RW.002 Nusa Beautiful Tamalanrea Against the Use of Traditional Medicine Increasing Body Resistance - H. Ambo Lau, Sulfiyana; Herman, Herman (Jurnal Farmasi Sandi Karsa, 2022)
One of the efforts to prevent COVID-19 is to increase the body's resistance. Basically, the human body has an immune system or immune system to fight viruses and bacteria that cause disease which can be maintained with the use of traditional medicine. This study aims to determine the level of knowledge of the community in RT.006/RW.002 Nusa Tamalanrea Indah on the use of immune-enhancing traditional medicines. This type of research is descriptive, namely research that includes surveys with data collection techniques in the form of filling out questionnaires. This research was conducted in Tamalanrea Indah Village, Makassar City, South Sulawesi in February-March 2022 with a total sample of 55 respondents with criteria 17-50 years old, able to communicate well, willing to be interviewed and physically and mentally healthy. The results of the study in RT.006/RW.002 Nusa Tamalanrea Indah concluded that the largest number of respondents were 29 women (52.73%), the data on the age of the most respondents were aged 31-50 years amounted to 20 people (36.36%). data on the work of the most respondents, namely household workers, other jobs and not working each 12 people (21.82%), respondents' knowledge of traditional medicinal plants to increase endurance are ginger, turmeric, lemongrass and moringa leaves. The most used part of the plant is the leaves. The most used processing method is by boiling and the percentage of knowledge is 97.18%. Based on the results of the study, it can be concluded that the level of knowledge of the community in RT.006/RW.002 Nusa Tamalanrea Indah towards the use of traditional medicine for increasing endurance is relatively high.